Effect of ripening stage and vacuum pressure on vacuum impregnated mango 'Chok Anan' - Phianmongkhol A. (2017)
© All Rights Reserved. Mango is a climacteric fruit that has attractive color, delicious taste and provides high contents of ascorbic acid and phenolic compounds. In the current study, mango 'Chok Anan' at different ripening stages was subjected to a vacuum impregnation process at various vacuum pressures (between 50 and 1013.25 mbar). The flesh of mango fruit was cut into 3.0x2.0x1.0 cm 3 , vacuum impregnated with sucrose solution for 10 min at room temperature, left for another 10 min in the sucrose solution at atmospheric pressure, removed from the solution and analyzed for its physicochemical characteristics. Collected data showed that the ripening stage of the mango affected color values of a* and b*, pH, hardness and solid gain (SG) of the vacuum impregnated mango. Different vacuum pressures that applied to mango pieces influenced fruit porosity (ε r ) and effective porosity (ε e ) of the final mango product. On the other hand, a combination of both parameters studied in the research had a significant effect on a color value of L*, water loss (WL), volume of fruit occupied by impregnation solution (X value) and fruit volume deformation (γ value) of the processed mango. The pieces of unripen mango impregnated at 50 mbar significantly had the lowest ε r of 0.03±0.01%, the lowest WL of -14.63±0.74% and the highest X value of 0.22±0.02 m 3 liquid/m 3 sample (p < 0.05). Finding in this study demonstrated that the ripening stage and vacuum pressure levels were important parameters to be considered in the application of vacuum impregnation to introduce desirable solute into a porous structure of fruit.